ASPECTS OF MATHEMATICAL MODELING AND INTERPRETATION OF A MANUFACTURING SYSTEM - Mihaela ALDEA; Elisabeta Mihaela CIORTEA (Fiabilitate şi Durabilitate)
In the paper developing we started from a model that allows a detailed decoding of causalrelationships and getting the laws that determine the evolution of the phenomenon.The model chosen for the study is a discrete event system applicable to optimize the transport systemused in pottery. In order to simulate the manufacturing process we chose Matlab package that contains pntoollibrary, by which can be realized modeling of analyzed graphs. Since the timings of manufacture are very highand the process simulation is conducted with difficulty, we divided the graph according to the transport system.